2000
DOI: 10.1086/301338
|View full text |Cite
|
Sign up to set email alerts
|

Binary Star Differential Photometry Using the Adaptive Optics System at Mount Wilson Observatory

Abstract: We present photometric and astrometric results for 36 binary systems observed with the natural guide star adaptive optics system of the Mount Wilson Institute on the Hooker 100-in telescope. The measurements consist of differential photometry in U, B, V, R and I filters along with astrometry of the relative positions of system components. Magnitude differences were combined with absolute photometry found in the literature of the combined light for systems to obtain apparent magnitudes for the individual compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 31 publications
7
62
0
Order By: Relevance
“…This method is similar to what the routine fitstars, presented in ten Brummelaar et al (1996Brummelaar et al ( , 2000, does to calculate the photometry of binaries. In the following paragraphs we describe this method in more detail.…”
Section: Photometry With Irdismentioning
confidence: 99%
“…This method is similar to what the routine fitstars, presented in ten Brummelaar et al (1996Brummelaar et al ( , 2000, does to calculate the photometry of binaries. In the following paragraphs we describe this method in more detail.…”
Section: Photometry With Irdismentioning
confidence: 99%
“…After reducing each image, we measured the astrometry and photometry using the fitstars algorithm on each image (ten Brummelaar et al 1996Brummelaar et al , 2000. Photometric error bars were set equal to the standard deviation of the measurements from all the images.…”
Section: Keck II Observationsmentioning
confidence: 99%
“…A recent review of modern approaches to AO photometry by Burke et al (2009) demonstrated that methods utilizing static, deterministic PSF should not be dismissed against more modern algorithms like iterative blind deconvolution (ten Brummelaar et al 2000). Therefore, we set out to test whether a modern implementation of the Richardson-Lucy-type deconvolution conserves the flux when given a mismatched AO PSF.…”
Section: Introductionmentioning
confidence: 99%